Generative reproduction of Vaccinium myrtillus in laboratory conditions and the influence of zinc-smelter emissions on it - Zuzanna Czuchajowska; Teresa Strączek (Acta Societatis Botanicorum Poloniae, 2014)
The germination of Vaccinium myrtillus seeds and the development of the seedlings in laboratory conditions are described. The dynamics, the power of germinaltion and Pieper coefficients for the seeds were strongly influenced by the intensity of zinc-,smelter pollution of the forest stand from which they originated. The rates of survival were also estimated for seedlings transferred from filter-;paper into polluted and unpolluted samples of soil and litter. The differences noticed in the latter parameter point to the possibility of formation in the polluted stand of ecotypes more resistant to the influence of pollution than the original ones.